Предмет:
МатематикаАвтор:
аноним1. 2 • x - 3,5 • (x - 4) = 6;
2 • х - 3,5 • х + 3,5 • 4 = 6;
-1,5 • х = 6 - 14;
-1,5 • х = -8;
х = -8 : (-1,5);
х = -8 : (-1 1/2) = -8 : (-3/2);
х = 16/3 = 5 1/3.
Ответ: х = 5 1/3.
2. 0,5 • (x - 2) + 2,3 • x = 5 • x - 4;
0,5 • х - 0,5 • 2 + 2,3 • х = 5 • х - 4;
2,8 • х - 1 = 5 • х - 4;
2,8 • х - 5 • х = - 4 + 1;
-2,2 • х = -3;
х = -3 : (-2,2) = -3 : (-2 1/5) = -3 : (-11/5);
х = 15/11 = 1 4/11.
Ответ: х = 1 4/11.
3. 2,4 • (x - 3) - 4 • x = 1 - x;
2,4 • х - 2,4 • 3 - 4 • х = 1 - х;
-1,6 • х - 7,2 = 1 - х;
-1,6 • х + х = 1 + 7,2;
-0,6 • х = 8,2;
х = 8,2 : (-0,6) = 8 1/5 : (-3/5) = 41/5 : (-3/5);
х = -41/3 = -13 2/3.
Ответ: х = -13 2/3.
Автор:
thumperepmjДобавить свой ответ
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть
Предмет:
Другие предметыАвтор:
анонимОтветов:
Смотреть
Предмет:
МатематикаАвтор:
анонимОтветов:
Смотреть